Investing in development : lessons of World Bank experience - Baum, Warren C.; Tolbert, Stokes M.; World Bank. (New York : Published for the World Bank [by] Oxford University Press, 1985)
This book critically explains the activities of human capital in developing countries with emphasis to how resources are managed.
Includes bibliographical references and index.
oo 14/01/19
Loans
Keywords: Investments, Foreign